OP0211 Association between Systemic Activity and Lymphoma in Primary Sjogren Syndrome: Baseline Essdai Predictors in 921 Spanish Patients (GEAS-SS Registry). (10th June 2014) - Brito Zeron, P.; Kostov, B.; Solans, R.; de Luna, G.; Casanovas, A.; Díaz-Lόpez, B.; Rascόn, F.J.; Qanneta, R.; Pérez-Alvarez, R.; García-Sánchez, I.; Ripoll, M.; Pinilla, B.; et al.
Abstract : Objectives: To analyse the epidemiological, clinical and analytical features at diagnosis and the usefulness the new 2010 European activity index (ESSDAI) to predict the development of lymphoproliferative disease in a large cohort of Spanish patients with primary Sjogren syndrome (pSS). Methods: The GEAS-SS multicenter registry was formed in 2005 with the aim of collecting a large series of Spanish patients with pSS, and included 12 Spanish reference centers with substantial experience in the management of SS patients. By November 2013, the database included 921 consecutive patients fulfilling the 2002 classification criteria for pSS. The cumulated ESSDAI index (2010 EULAR-SS disease activity index) was retrospectively calculated at diagnosis. Statistical values were expressed as the hazard ratio (HR) and 95% confidence interval (CI) for death. Results: After excluding 17 patients who were diagnosed with lymphoma before SS diagnosis, we evaluated a total of 904 patients who were followed a mean of 79 months: 25 (3%) patients developed lymphoproliferative disease after being diagnosed with pSS. The following baseline features at diagnosis were associated with the development of lymphoma: male gender (HR 5.78, CI 2.14-15.63), age (HR 1.04, CI 1-1.07), C3 values <0.82 g/L (HR 3.75, CI 1.38-10.19), C4 values <0.07 g/L (HR 3.22, CI 1.08-9.61), monoclonal serum band (HR 4.23, CI 1.38-13.02) and cryoglobulins (HR 4.44, CI 1.86-10.58). Multivariate Cox proportional-hazards regression analysis identified gender, low C3, monoclonal band and cryoglobulins as significant independent variables related to lymphoma. With respect to the ESSDAI domains, activity (score ≥1) in the constitutional (HR 4.06, CI 1.54-10.70) and hematological (HR 2.59, CI 1.16-5.78) domains was associated with the development of lymphoma, and the hematological activity was independently associated with lymphoma development. In the constitutional domain, patients with the highest activity degree (fever >38.5°C/night sweats and/or involuntary weight loss of >10% of body weight) showed the high risk of development of lymphoma (HR 9.11, CI 2.51-33.12). No statistical associations were found between the remaining domains or the total ESSDAI score and the risk of lymphoma. Conclusions: Fever >38.5°C, night sweats and/or significant weight loss were the key clinical features prospectively associated with the development of lymphoproliferative disease in patients with pSS. In addition, we identified a specific hematological and immunological profile (cytopenias, hypocomplementemia, monoclonal band and cryoglobulinemia) as laboratory predictors of hematological neoplasia in SS. Patients presenting with this clinical and laboratory profile at diagnosis of pSS need a closer follow-up. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5008